2009
DOI: 10.1590/s1517-83822009000300012
|View full text |Cite
|
Sign up to set email alerts
|

A defective mutant of Salmonella enterica Serovar Gallinarum in cobalamin biosynthesis is avirulent in chickens

Abstract: Salmonella enterica serovar Gallinarum (SG) is a fowl typhoid agent in chickens and is a severe disease with worldwide economic impact as its mortality may reach up to 80%. It is one of a small group of serovars that typically produces typhoid-like infections in a narrow range of host species and which therefore represents a good model for human typhoid. The survival mechanisms are not considered to be virulent mechanisms but are essential for the life of the bacterium. Mutants of Salmonella Gallinarum contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Currently, live vaccines (LV) against SG are frequently used in the fields. The attenuated strains are able to colonize internal organs, without clinical symptoms, however they induce an efficient immune response (DE PAIVA et al, 2009;LEE et al, 2005;SHEHATA et al, 2013). The use of LV prepared with attenuated strains of SG has showed good immunogenicity and capacity to induce a strong cellular and humoral immune response in experimental models (MATSUDA et al, 2011a;2011b;PENHA FILHO et al, 2012).…”
Section: Palavras-chavementioning
confidence: 99%
See 1 more Smart Citation
“…Currently, live vaccines (LV) against SG are frequently used in the fields. The attenuated strains are able to colonize internal organs, without clinical symptoms, however they induce an efficient immune response (DE PAIVA et al, 2009;LEE et al, 2005;SHEHATA et al, 2013). The use of LV prepared with attenuated strains of SG has showed good immunogenicity and capacity to induce a strong cellular and humoral immune response in experimental models (MATSUDA et al, 2011a;2011b;PENHA FILHO et al, 2012).…”
Section: Palavras-chavementioning
confidence: 99%
“…Mutant strain of SG with deleted genes cobS and cbiA (SGΔcobSΔcbiA), attenuated for commercial chickens, was constructed according to the previously described (DE PAIVA et al, 2009) and used LV. The construction and use of the mutant strain was approved by the National Technical Committee of Biosecurity (Protocol no.…”
Section: Inoculums and Vaccinesmentioning
confidence: 99%
“…The live vaccine (LV) consisted of the attenuated SGΔcobSΔcbiA (de Paiva et al, 2009;Penha Filho et al, 2010), resistant to kanamycin. An invasive highly pathogenic SG strain (SG 287/91), kindly donated by Prof. Paul Barrow (University of Nottingham, UK) was used to challenge birds.…”
Section: Bacterial Strains and Vaccinesmentioning
confidence: 99%
“…The strain SGΔcobSΔcbiA is a mutant strain of SG 287/91, with deletion on genes cobS and cbiA, previously shown to be attenuated and capable to colonize internal organs, in reduced numbers in comparison with wild SG strain (de Paiva et al, 2009). Previous studies have also shown that this strain is immunogenic and one vaccine dose elicited protection against SG and cross protection against S. Enteritidis (Penha Filho et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The description of the construction of the attenuated nalidixic acid-resistant strain of Salmonella Gallinarum, carrying deletion on cobS and cbiA genes (SGDcobSDcbiA) was described by Paiva et al (2009b). A pathogenic strain of Salmonella Gallinarum resistant to nalidixic acid was used to challenge the brown layers and a pathogenic strain of Salmonella Enteritidis resistant to nalidixic acid and spectinomycin was used to challenge the white-egg layers.…”
Section: Bacterial Strainsmentioning
confidence: 99%